Relación entre el razonamiento y la resolución de los problemas en ciencia tecnología y ambiente de los estudiantes del 5to grado de secundaria de la I.E Divino Maestro - Dávila Samamé, Kelly (2010)
The investigation had for aim determine the relation that there exists between the reasoning and the resolution of problems in Science Technology and Environment of the students of the fifth degree of secondary education of the Educational lnstitution " Divine Teacher" of the district Elias Soplín Vargas of the province of Rioja in the year 201 O. The field information was gathered of 36 students, using two instruments of compilation of information a test of reasoning: deductive and inductive and a test of resolution of problems. The analysis of the results was realized across the distribution of frequencies and the coefficient of correlation of Pearson, the contrastación of hypothesis was realized following the law of t Student with N-2 degrees of freedom to 5 % of the level of significancia. The results demonstrate, in judging form, that the students present moderate level of reasoning and high level of resolution of problems, demonstrate also that exists significant relation between the reasoning and the resolution of problems in Science Technology and Environment of the students of the fifth degree of secondary education of the Educational lnstitution " Divine Teacher ", with coefficient of correlation 0,90 and with, t calculated, tc=12,6, majar to t tabulated, tt=2,05.